The Implementation of Immediate Feedback in Problem-based Learning: The Problem-Solving Skill Analysis Seen from Self-Efficacy (Unnes Journal of Mathematics Education Research, 2022)
One of the common problems faced by some students in learning mathematics is: low in answering questions related to problem solving. The purpose of this study was to describe the problem-solving ability of students through immediate feedback on learning Problem-based Learning in terms of self-efficacy of students. This research was conducted with a qualitative descriptive approach. The research subjects of Class X Mathematics and Natural Sciences 3 SMA Negeri 2 Grabag academic year 2021/2022 were 36 people. This study uses a problem based learning model with immediate feedback. Data were collected by test, questionnaire, observation, documentation, and interview methods. The results of problem-solving ability test achievement of students in terms of self-efficacy in learning problem-based learning with immediate feedback are quite varied. Problem-solving ability reviewed self-efficacy showed that students with high problem-solving ability test and self-efficacy categories could understand and master the four indicators, students with medium problem-solving ability test and self-efficacy categories could understand and master the three indicators, and students with low problem-solving ability test and self-efficacy categories can understand and master both indicators.